(untitled) (Social Science Review, 2022)
The COVID-19 pandemic of 2020 has influenced human health and society alike. Among others, the Knowledge, Attitude and Practice (KAP) model is an important sociological tool to understand the response and prepare the preventive strategies in a global pandemic. This study aims to investigate the relevance of the KAP model to understand the COVID-19 pandemic situation by measuring participant’s knowledge and outlook towards the pandemic and eventually how this results in their everyday practice. An online cross-sectional survey was carried out among university students of Bangladesh. Data were collected during the onset of the pandemic: March-April 2020. The finding reveals the KAP model shows relatively low success in explaining the COVID-19 situation in Bangladesh’s social context. Besides, existing features of the KAP model can hardly shed light on the diversity of socio-economic conditions, strong prevalence of intersectionality, evolving nature and multidimensionality of knowledge. By showing some limitations of the KAP model, this study suggests going beyond the KAP model (if necessary) to understand the complexity of the COVID-19 condition, which in turn widens its scope for further improvement. Social Science Review, Vol. 38(1), June 2021 Page 33-52